Interventions delivered in secondary or tertiary medical care settings to improve routine vaccination uptake in children and young people: a scoping review. Issue 8 (2nd August 2022) - Blagden, Sarah; Newell, Kathryn; Ghazarians, Nareh; Sulaiman, Sabrena; Tunn, Lucy; Odumala, Michael; Isba, Rachel; Edge, Rhiannon
Abstract : Objective: To identify and analyse the interventions delivered opportunistically in secondary or tertiary medical settings, focused on improving routine vaccination uptake in children and young people. Design: Scoping review. Search strategy: We searched CINAHL, Web of Science, Medline, Embase and Cochrane Database of Systematic Reviews for studies in English published between 1989 and 2021 detailing interventions delivered in secondary or tertiary care that aimed to improve childhood vaccination coverage. Title, abstract and full-text screening were performed by two independent reviewers. Results: After deduplication, the search returned 3456 titles. Following screening and discussion between reviewers, 53 studies were included in the review. Most papers were single-centre studies from high-income countries and varied considerably in terms of their study design, population, target vaccination, clinical setting and intervention delivered. To present and analyse the study findings, and to depict the complexity of vaccination interventions in hospital settings, findings were presented and described as a sequential pathway to opportunistic vaccination in secondary and tertiary care comprising the following stages: (1) identify patients eligible for vaccination; (2) take consent and offer immunisations; (3) order/prescribe vaccine; (4) dispense vaccine; (5) administer vaccine; (6) communicate with primary care; and (7) ongoing benefits of vaccination. Conclusions: Most published studies report improved vaccination coverage associated with opportunistic vaccination interventions in secondary and tertiary care. Children attending hospital appear to have lower baseline vaccination coverage and are likely to benefit from vaccination interventions in these settings. Checking immunisation status is challenging, however, and electronic immunisation registers are required to enable this to be done quickly and accurately in hospital settings. Further research is required in this area, particularly multicentre studies and cost-effectiveness analysis of interventions.